What is the impact of a Confucian welfare regime upon lone mothers in Taiwan ? - Lee, Ming-Yu (2001)
This study explores the impact of a Confucian Welfare Regime upon lone mothers in Taiwan, where the family is promoted as the major welfare provider for individuals. Since the 1980s, politicians and welfare scholars --whether New Right or Third-Way-- in the West, particularly in the UK, have been very keen to draw lessons from the Confucian Welfare Model in East Asia. The characteristics of this welfare regime are categorised as "conservative corporatism without Western-style worker participation, solidarity without equality, laissez-faire without libertarianism, far too much social control but too little citizenship, far too little state intervention in welfare provision but too much familial welfare responsibilities"(e. g., Jones 1993). The Confucian Welfare State is in fact much deeply familialised, and the family is "the super-major welfare provider" compared to Western welfare states. This thesis will examine the Confucian Welfare Regime from the point of views of gender, and will argue that its distinctive fractures cannot be understood within existing Western comparative typologies and have not been adequately analysed in East Asian studies.